Machinability study on drilling austenite stainless steel 316l1 using minimum quantity lubrication (MQL) on surface roughness - Zuraifah, Kamarudin (2012)
This research was carried out to determine the optimum condition of cutting speed, feed rate and point of angle while drilling the austenite stainless steel in order to get the good surface finish by using Minimum Quantity Lubrication (MQL). This project focuses on the drilling small hole on the austenite stainless steel by using milling machine. The aim of this project is to find the optimum condition in producing the good surface finish in drilling process with MQL. The Taguchi OA from software Minitab 16 was used to formulate the experiment, to analyze the three factors and also to predict the optimal choices of the drilling parameters. The selected cutting speeds for the drilling process are 15m/min, 25m/min and 35m/min. For the feed rate, the parameters are 0.1mm/rev, 0.15mm/rev and 0.2mm/rev. The third parameter that will be considered in this project is point of angle, and the parameters that will be used are about 110°, 120° and 135°. The machining processes were performed on the CNC milling machine. The surface roughness will be test by using Surfcom 130A. Results shows that, the best surface roughness were obtained at the lower cutting speed, middle of feed rate and middle of point of angle. So, the optimum cutting speed, feed rate and point of angle are, 15m/min, 0.15mm/rev and 120°. The confirmation results show that, the predicted values and the measured values are quite close to each other.